Driving Millennial Satisfaction in L-Commerce: Perceived Price Advantage, Real-Time Interactivity, and Perceived Visibility as Key Factors - Sah, Tomi (Pusat P2M Politeknik Negeri Batam, 2024)
The advent of Live-Commerce has spurred changes in consumer shopping preferences. Millennials play a pivotal role in current consumer trends, being highly digitally active and predominant users across various online platforms. The objective of this study is to investigate how three dimensions of Live-Commerce including perceived price advantage, real-time interactivity, and perceived visibility affect millennial satisfaction in the context of online shopping within Live-Commerce platforms. Employing a quantitative approach, this study utilizes multiple linear regression analysis to identify factors influencing millennial consumer satisfaction. The findings reveal that perceived price advantage, real-time interactivity, and perceived visibility partially and significantly impact millennial satisfaction in live commerce, with perceived price advantage emerging as the most dominant factor. The findings of this study provide both theoretical insights and practical implications for advancing Live-Commerce enterprises within the province of Bangka Belitung Islands.